The manager's guide to building a successful business - Randazzo, Gary (2013 digital library., 2013)
This uses real market examples to demonstrate the effective use of management and marketing principles. The book also introduces programs developed over a 40-year career to help manage all aspects of a business and to develop and execute marketing strategies. Managers and executives will use this book as a guide to grow an established business or start a new one. The book can be used as a reference book for unique management challenges as well.